Sistema de pagamentos em moeda local: uma estratégia do Mercosul perante a hegemonia do dólar? - Pithan, Bruna Dias (2025)
This research examines the Mercosur Local Currency Payment System (SML) as a strategy to reduce dependence on the US dollar in economic transactions among Mercosur member countries, assessing its potential to promote economic autonomy and financial stability within the bloc. Using a qualitative approach, the study relies on document analysis of Mercosur agreements, meeting minutes, trade data, and specialized literature on international political economy. The findings indicate that while the SML facilitates intra-bloc transactions and reduces exchange costs, its effectiveness is limited by economic asymmetries and political divergences among member states. It is concluded that the mechanism holds relevance as an alternative to dollar hegemony but requires stronger regulatory coordination and institutional commitment to achieve its objectives.